Realization of 1D Classic Heisenberg Spin-Glass System on GPU - Abajyan, Hakob G. (Mathematical Problems of Computer Science, 2021)
New high performance parallel algorithm for simulation of 1D classic Heisenberg spin-glass system is developed. The realization is done on Graphics Processing Units (GPU). Numerical simulations of the classic Heisenberg spin glass model show that this is a good example of applications that may benefit of the GPU computing capabilities. GPU performance time and memory statistics are presented.